2019
DOI: 10.1136/sextrans-2017-053363
|View full text |Cite
|
Sign up to set email alerts
|

The Denominator problem: estimating the size of local populations of men-who-have-sex-with-men and rates of HIV and other STIs in Switzerland

Abstract: ObjectivesThere is no estimate of the current number of men who have sex with men (MSM) in Switzerland, or of their geographical distribution. We aimed to (1) estimate MSM concentration factors and population sizes for 83 Swiss postal code areas (PCA), including the nine largest Swiss cities, and (2) calculate MSM-specific local HIV prevalence and yearly rates of diagnosed HIV, hepatitis C virus (HCV), syphilis and gonorrhoea.MethodsWe triangulated data from general population estimates, MSM online surveys, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
(21 reference statements)
1
25
0
1
Order By: Relevance
“…In our study, however, HIV events were found to occur exclusively in MSM, which raises the additional question whether MSM should be encouraged to transition to PrEP as early as after a first PEP episode. Early transition is also supported by the fact that, compared to HIV incidence rates in the overall MSM population of Zurich (average 2010-2013: 39 per 10,000) 20 , rates retrieved from our study were higher in PEP-seeking MSM (70.5 per 10,000) and in MSM with repetitive PEP seeking (81.1 per 10,000; assuming that all HIV events were captured, and that all participants presumed HIV negative were still at risk at the time of analysis-Supplementary table 1). Although some institutions may have already started considering first PEP-episodes in MSM as an indication for PrEP (as it is currently the case at the USZ), the exact timing of referral to PrEP programs is still lacking in most national and international recommendations 18,21,22 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, however, HIV events were found to occur exclusively in MSM, which raises the additional question whether MSM should be encouraged to transition to PrEP as early as after a first PEP episode. Early transition is also supported by the fact that, compared to HIV incidence rates in the overall MSM population of Zurich (average 2010-2013: 39 per 10,000) 20 , rates retrieved from our study were higher in PEP-seeking MSM (70.5 per 10,000) and in MSM with repetitive PEP seeking (81.1 per 10,000; assuming that all HIV events were captured, and that all participants presumed HIV negative were still at risk at the time of analysis-Supplementary table 1). Although some institutions may have already started considering first PEP-episodes in MSM as an indication for PrEP (as it is currently the case at the USZ), the exact timing of referral to PrEP programs is still lacking in most national and international recommendations 18,21,22 .…”
Section: Discussionmentioning
confidence: 98%
“…Most notably, a series of longitudinal surveys among MSM found that between 2007-2014, PEP uptake ranged between 2.6 and 8% (mean: 5%) 28 . According to a previous report combining several data sources to estimate the size of local MSM populations 20 , the number of MSM in the Zurich area was 16000 (95% credible interval: 14,300-16,500). Combining results on PEP uptake with local MSM population estimates corresponded to an estimated number of 416 to 1280 (mean: 800) PEP prescriptions occurring in Zurich within that timeframe.…”
Section: Discussionmentioning
confidence: 99%
“…Our model population comprised all MSM in Switzerland from 2006 to 2018. We estimated the number of MSM in Switzerland between 2006 and 2018 based on the demographic dynamics of Switzerland by the Federal Statistical Office, Switzerland and Schmidt and Altpeter, 2019[12,13]. In Switzerland, all syphilis cases are anonymously reported to the Federal Office of Public Health (FOPH)[4].…”
Section: Methodsmentioning
confidence: 99%
“…We define MSM as men who are attracted to other men or who have sex with men, regardless of whether they identify themselves as gay. The population of MSM aged 15–65 in Switzerland (2012) is estimated to be 80 000 (Bayesian 95% credibility interval 64 000 to 96 000) of whom about half live in the five largest cities (Zurich, Geneva, Basel, Lausanne and Bern) 11…”
Section: Methodsmentioning
confidence: 99%
“…Those with undiagnosed HIV infection are among about 20% of MSM in Switzerland who report never having had an HIV test during their life or among the 60% who have not had a test in the last year 10. We estimate that in 2012, 6300 MSM (8%) were living with HIV both diagnosed and undiagnosed, and 1700 (or 2.2%) had non-suppressed HIV infection 11. In addition, an increasing proportion of MSM report condomless anal intercourse with one or more casual sex partners 10…”
Section: Introductionmentioning
confidence: 99%